55 Effects of concentrate supplementation frequency and amount on growth and reproductive performance of Brangus heifers. (28th November 2020) - Palmer, Elizabeth; Vedovatto, Marcelo; Ranches, Juliana; Oliveira, Rhaiza; Arthington, John; Vendramini, Joao; Moriel, Philipe
Abstract: A 2-yr study evaluated the impacts of supplementation frequency and amount on growth and puberty attainment of Brangus heifers. On d 0 of each year, 64 Brangus heifers were stratified by BW and age (244 ± 4 kg; 311 ± 18 d) and assigned to 1 of 16 bahiagrass pastures (4 heifers/pasture). Treatments were randomly assigned to pasture (4 pastures/treatment) in a 2 × 2 factorial design and consisted of heifers offered a soybean hulls-based supplement DM at 1.25% or 1.75% of BW delivered either daily (7X) or 3 times weekly (3X; Monday, Wednesday, and Friday). On d 56, heifers were inserted with a CIDR device for 14 d, followed by administration of PGF2α and a timed-AI+GnRH protocol on d 89. Heifers were exposed to bulls from d 89 to 167. Data were analyzed using the SAS GLIMMIX procedure. No rate × frequency interactions were detected (P ≥ 0.20). Overall ADG was greater for 7X vs. 3X heifers (P = 0.007). Daily supplementation increased (P ≤ 0.03) the percentage of pubertal heifers prior to CIDR insertion and at AI compared to 3X supplementation; however, percentage of pregnant heifers did not differ (P = 0.70). Supplementation at 1.25% vs. 1.75% enhanced the overall ADG (P = 0.02) but did not impact (P = 0.18) the percentage of pubertal heifers before CIDR insertion. After the puberty induction protocol, heifers supplemented at 1.75% of BW achieved greater puberty attainment at time of AI (P = 0.05) and final pregnancy rates (P = 0.02) than heifers supplemented at 1.25% of BW. When a puberty induction protocol was included, the percentage of pregnant Brangus heifers were not affected by supplementation frequency (daily vs. 3 times weekly) but enhanced when the supplement dry matter amount was offered at 1.75 vs. 1.25% of body weight.